PERENCANAAN DAN PERANCANGAN PUSAT REHABILITASI NARKOBA DI DENPASAR: Bahasa Indonesia - Sidhi, I Gede Mas Giri Hari Purnama; Putra, I Nyoman Gede Maha; Hartawan, I Putu; Wijaya, I Kadek Merta; Wiguna, Made Mas Surya (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
Rehabilitation is a program that aims to help sufferers of chronic illnesses, both physical and psychological, to recover. The Rehabilitation Center uses a variety of different methods for the patient, treatment is adjusted according to the patient's illness and the intricacies from the start of the patient. The patients who enter the rehabilitation center mostly suffer from low self-esteem and lack of positive outlook on life, therefore psychology plays a very big role in the Rehabilitation program, and it is also very important to protect the patient from friends and environments that allow the addiction to return against illegal drugs.